Development of the Voluntary Accreditation for Study Programmes in Russia - O. A. Matveeva (Высшее образование в России)
The article addresses the study of supply and demand in the field of independent voluntary accreditation of study programmes delivered by higher education institutions in Russia. The paper presents the results of the analysis of the activity of Russian and foreign accreditation organizations as well as the analysis of the effectiveness of the national monitoring system for professional and public accreditation and European quality assurance register for higher education EQAR. In author’s opinion, the current state of public accreditation is characterized not so much by the “accreditation boom” on the part of higher education institutions, as by the “accreditation bubble” on the part of accreditation organizations. At the same time, strict requirements for accreditation organizations that are included into European quality assurance register for higher education provide confidence and recognition for independent international accreditation, which makes it increasingly in demand, especially among the country’s leading universities. The paper dwells on the following trends in the development of independent accreditation procedures: 1) during the current decade the accreditation process is gaining momentum, which is characterized by the growth of number of accreditation organizations as well as educational institutions interested in obtaining accreditation; 2) the state supports and encourages the development of the independent accreditation system for quality assurance in higher education; 3) the voluntary accreditation enables educational organizations to get an independent assessment of study programmes and thus to receive “a bonus” before a state accreditation procedure; 4) the database of External Quality Assurance Reports (DEQAR) becomes a preferred instrument for higher education institutions, whereas they are interested in raising their transparency related to the quality of study programmes and their competitiveness in the global educational space.